The Relationship Between EFL Students' Implicature Competence and Their English Academic Success Across Gender - Amirreza Namdari; Alireza Bonyadi (Journal of Pragmatics Research, 2024)
Implicature, a fundamental aspect of pragmatics, plays a significant role in effective communication. Investigating the implicature competence in the realm of English as a Foreign Language (EFL) education, the present paper aims at exploring the relationship between implicature competence and English academic success of EFL students across gender. The study included 60 EFL learners aged between 13 and 22, comprising both male and female students enrolled in Jahad Daneshgahi Department of Foreign Languages in West Azerbaijan, Urmia. To investigate the relationship, a quantitative correlation design was employed, utilizing MCDCT (Multiple-Choice Discourse Completion Test) to measure implicature competence of the students. The results revealed a positive correlation between implicature competence and academic success of EFL students. However, the correlation was more significant in male students than their female counterparts. These findings emphasize the importance of explicit teaching of pragmatics along with other linguistics skills in EFL curricula.